Children preferences of coloured fresh cheese prepared during an educational laboratory - Federica Tesini; Monica Laureati; Rosa Palagano; Mara Mandrioli; Ella Pagliarini; Tullia Gallina Toschi (Chiriotti Editori, 2015)
Choices among young consumers are mainly driven by food preferences; in particular, a connection between appearance and acceptance of food has been highlighted, together with a general lack of knowledge of food processing. For these reasons, educational activities are important to increase scientific knowledge and awareness. The cheese-making educational laboratory described herein involved children, adolescents, and their parents/teachers in the preparation of fresh and naturally-coloured cheeses. At the end of the activity, both the colour preference and possible relation between preference and colour of cheese prepared were investigated administering a short questionnaire.